Fluconazole-loaded solid lipid nanoparticles topical gel for treatment of pityriasis versicolor: formulation and clinical study - Shaimaa El-Housiny; Maii Atef Shams Eldeen; Yasmina Ahmed El-Attar; Hoda A. Salem; Dalia Attia; Ehab R. Bendas; Mohamed A. El-Nabarawi (Taylor & Francis Group, 2018)
Solid lipid nanoparticles (SLNs) are very potential formulations for topical delivery of antifungal drugs. Hence, the purpose of this research was to formulate the well-known antifungal agent Fluconazole (FLZ)-loaded SLNs topical gel to improve its efficiency for treatment of Pityriasis Versicolor (PV). FLZ-SLNs were prepared by modified high shear homogenization and ultrasonication method using different concentration of solid lipid (Compritol 888 ATO, Precirol ATO5) and surfactant (Cremophor RH40, Poloxamer 407). The physicochemical properties and the in vitro release study for all FLZ-SLNs were investigated. Furthermore, the optimized FLZ-SLN formula was incorporated into gel using Carpobol 934. A randomized controlled clinical trial (RCT) of potential batches was carried out on 30 well diagnosed PV patients comparing to market product Candistan® 1% cream. Follow up was done for 4 weeks by clinical and KOH examinations. The results showed that FlZ-SLNs were almost spherical shape having colloidal sizes with no aggregation. The drug entrapment efficiency ranged from 55.49% to 83.04%. The zeta potential values lie between −21 and −33 mV presenting good stability. FLZ showed prolonged in vitro release from SLNs dispersion and its Carbapol gel following Higuchi order equation. Clinical studies registered significant improvement (p < .05) in therapeutic response (1.4-fold; healing%, 4-fold; complete eradication) in terms of clinical cure and mycological cure rate from PV against marketed cream. Findings of the study suggest that the developed FLZ loaded SLNs topical gels have superior significant fast therapeutic index in treatment of PV over commercially available Candistan® cream.